Early administration of Fab antivenom resulted in faster limb recovery in copperhead snake envenomation patients. (2nd January 2019) - Anderson, Victoria E.; Gerardo, Charles J.; Rapp-Olsson, Malin; Bush, Sean P.; Mullins, Michael E.; Greene, Spencer; Toschlog, Eric A.; Quackenbush, Eugenia; Rose, S. Rutherfoord; Schwartz, Richard B.; Charlton, Nathan P.; Lewis, Brandon; et al.
Abstract: Background: No previous research has studied whether early snake antivenom administration leads to better clinical outcomes than late antivenom administration in North American pit viper envenomation. Methods : A secondary analysis of data from a clinical trial of Fab antivenom (FabAV) versus placebo for copperhead snake envenomation was conducted. Patients treated before the median time to FabAV administration were classified as receiving early treatment and those treated after the median time were defined as the late treatment group. A Cox proportional hazards model was used to compare time to full recovery on the Patient-Specific Functional Scale (PSFS) instrument between groups. Secondary analyses compared estimated mean PSFS scores using a generalized linear model and the estimated proportion of patients with full recovery at each time point using logistic regression. To evaluate for confounding, the main analysis was repeated using data from placebo-treated subjects. Results : Forty-five subjects were treated with FabAV at a median of 5.47 h after envenomation. Patients in the early treatment group had a significantly shorter time to full recovery than those treated late (median time: 17 versus 28 days, p  = .025). Model-estimated PSFS scores were numerically higher at each time point in the early group. No difference was found between patients treated early versus late with placebo. Conclusions : In this secondary analysis of trial data, recovery of limb function was faster when Fab antivenom was administered soon after envenomation, as opposed to late administration.